Periodization and Chronology of the Neolithic Upper Sukhona and Eastern Lake Onega Region - Nadezhda G. Nedomolkina (Археология евразийских степей)
The river network of the Vologda region is very dense and belongs to three basins: the White, Baltic and Caspian seas. This fact affects the cultural and historical development of different areas of the Vologda region already in ancient times. The Neolithic in the region has been studied by archaeologists unevenly. Currently, new archaeological settlements – have been identified and studied, data have been obtained from natural sciences, which have made it possible to expand and clarify ideas about the cultural and historical processes that took place in the territory of the Eastern Lake Onega region and Upper Sukhona, Lake Kubenskoye and to supplement our knowledge about the Stone Age of the Russian North – European North-East. Based on the results of studying these two parts of the region – the Eastern Lake Onega region and the Upper Sukhona – a chronology and periodization of the development of areas in the Neolithic is proposed.